The Effect Of Perceived Organizational Support And Intrinsic Motivation On Employee Engagement At PT. XYZ - Asyhabul Khairi, Rizki; Rinaldi, Rinaldi (CV. Causalita Dynamic Solutions, 2025)
This study aims to analyze the influence of perceived organizational support and intrinsic motivation on employee engagement at PT. XYZ, an outsourcing company located in Padang, Indonesia. The research employs a quantitative approach using a total sampling technique involving 74 employees as respondents. The research instruments consist of the Utrecht Work Engagement Scale (UWES-17), Eisenberger’s Perceived Organizational Support Scale, and Ryan & Deci’s Intrinsic Motivation Scale, which have been adapted accordingly. The results indicate that perceived organizational support and intrinsic motivation have a positive and significant impact on employee engagement, both partially and simultaneously. These findings emphasize the importance of organizational support, fairness, reward systems, supportive leadership, and the fulfillment of employees' psychological needs. This investigation yields actionable insights for developing evidence-based talent management approaches, offering organizations a robust framework to cultivate employee engagement participation. The findings illuminate three critical pathways for organizational development